Synthesis and Characterization of Mixed Ligand Complexes of Thorium(IV) with N,N'-Triethylenediamine-bis-(3-carboxypropenamide) and Various Anions - Viswanathan, M.; Krishnan, G. (Asian Journal of Chemistry, 2016)
The present research paper is concerned with the synthesis and characterization of some mixed ligand complexes of thorium(IV) with N,N'-triethylenediamine-bis-(3-carboxypropenamide) [TEBCPH2] and various anions such as nitrate, perchlorate and thiocyanate. The analytical data include determination of molecular mass, metal percentage, anion percentage, molar conductance, spectral and thermal studies. The complexes confirm the composition: [Th(TEBCP)X2] where X = NO3 or NCS– and [Th(TEBCP)CIO4]ClO4.